The Chinese Communist Party as a Global Force - Frank N. Pieke (Journal of Current Chinese Affairs, 2022)
The Chinese Communist Party (CCP) is currently in the throes of redefining itself as not just China's ruling party, but also as the dominant political force of global China. Following the path of Chinese globalisation, this project overlaps with – but is different from – China's much maligned strategy of influencing and interfering in the society and politics of other countries. The principal aim of the CCP's global extension is not to meddle in the affairs of other countries, but tying Chinese people, goods, money, business, and institutions that have ventured abroad back into the strategy and domestic system of China and the CCP. The article shows that China's emerging superpower is informed both by China's unique pattern of globalisation and the CCP's own understanding of the nature, aims, and modalities of its rule, which can only partially be compared to those of earlier superpowers.